(untitled) (International Journal of Engineering and Computer Science, 2015)
This research work is carried out to study wireless sensor networks (WSNs) are composed of many stumpy cost, little power devices with sensing, local processing and wireless communication capabilities. Minimizing energy dissipation and maximizing network lifetime are important issues in the design of routing protocols for sensor networks. The clustering algorithms are a kind of key technique used to reduce energy consumption, increase the scalability and lifetime of the network. Many routing protocols have been designed which have used the clustering mechanism to improve the energy efficiency and lifetime of the network. In the clustering protocols the cluster heads for every particular round are selected among the nodes that have the highest energy and they aggregate the data from their associated cluster members to transmit it to base station. Traditionally homogeneous networks are only used where the nodes have limited resources and limited computation capabilities as all the nodes are equipped with the same amount of energy and as a result, they cannot take full advantage of the presence of node heterogeneity. Heterogeneous networks are especially useful in extending the lifetime of the network, providing more stability to the network and increasing the throughput of the network, as here total energy of the network is increased due to node heterogeneity. Our protocol comprises of four level heterogeneity as here four types of nodes i.e normal, intermediate, advanced and superadvanced nodes are used to boost the network energy